Prarancangan Pabrik Etilen Dari Cracking Nafta Dengan Proses Maxene - Fikri Miftahul Shiddiq; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Ethylene produced by cracked the chain of various componen in naphtha. n-paraffin is preferable for thermal cracking reactor feed to produce ethylene. MaxEne process help to result n-paraffin rich stream as feed to thermal cracking reactor. The main equipment of MaxEne process is adsorbent chamber with n-butane as desorbent agent and two debutanizer, one of them is debutanizer extract column and the other one is debutanizer raffinate column. The purpose of this study is to determine the chemical design and mechanical design of debutanizer raffinate column also the economical analysis of plant. The chemical design of debutanizer raffinate column such us determination of the number of tray is using fenske methode. The main mechanical design of debutanizer raffinate column is to determine the design of support and flange. The economical analysis of the plant is determination of Cumulative Cash Ratio (CCR) and Present Value Ratio (PVR). The number of tray is 34. The heigt and diameter are 38,42 and 5,9 m respectively. The type of skirt is conical skirt with angle 83° to the base ring. The Thickness of the flange joint the head with shell is 0,85 m. The value of Cumulative Cash Ratio (CCR) and Present Value Ratio (PVR) are 2.2 and 1.29 respectively. Keywords : maxene, ethylene, thermal cracking, desorbent, n-paraffin